Analisis Kinerja dalam Melaksanakan Pengujian Kendaraan Bermotor pada Dinas Perhubungan Kabupaten Sidenreng Rappang - Sultan S Bafaddal (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Testing of motor vehicles is a series of government enforcement aimed to reduce the number of accidents caused by unpreserved vehicle, such as freight vehicles and public passenger vehicles. Data collection methods used in this research were (1) Observation, (2) Interview, (3) Questionnaire, and (4) Literature study. The collected data were analyzed through frequency tables and percentages. The population and sample took as many as 49 people using total sampling. The results showed that the ability of the personnels to carry out testing motor vehicles was in capable category (57,14%), while the motivation was in high category (59,18%). Further results showed the level of discipline which was high (61,22%), and a relatively good performance (63,27%). The supporting factors that affect performance in this study were the quality and performance quantity, the knowledge possessed by the testing personnels of the motor vehicle, and the toughness at work. While the limiting factor of performance in this research were the lack of discipline level, lack of skills and work performance, and lack of motivations.